145 Optico-spinal demyelination: not NMO or MS, what is it? A longitudinal cohort study. Issue 3 (9th February 2012) - Panicker, J; Das, K; Boggild, M; Jacob, A
Abstract : With the availability of Aquaporin-4 antibodies, patients with relapsing spinal cord and optic nerve syndromes can be classified as NMO spectrum disorders. Despite this, a number of patients remain who have idiopathic optico-spinal demyelination. Though small series of such patients have been reported data on the long-term outcome of these patients is sparse. Methods: From 2003 to 2005 cases of non-MS optico-spinal demyelination (ie, optic neuritis, myelitis and brain MRI not suggestive of MS) were reported via the British Neurological Surveillance Unit. Consenting patients and scans were reviewed and cases have been followed-up. Aquaporin-4 antibodies were assayed and patients were classified at 6 years into: NMO/NMO spectrum disorders, MS and optico-spinal demyelination—unclassified (OSD-U). Results: Of 128 patients screened, 67 were initially classified as non-MS, optico-spinal demyelination. On follow-up at a median of 3.2 years (0–5.5) 34 patients were diagnosed as NMO (2006 criteria), six patients had been re-classified as MS and 27 patients remained as OSD-U. Relapses in this latter group were limited to optic nerve and spinal cord. Spinal cord lesions did not extend beyond three vertebral bodies, CSF oligoclonal bands were absent in 18/27 (67%) and MRI brain remained normal or atypical for MS on follow-up. Conclusions: On follow-up around 20% of patients with optico-spinal demyelinating disorders cannot currently be easily classified. It is possible that idiopathic optico-spinal demyelination is a distinct entity or a sub-group of either MS or NMO. Longer clinical follow with repeat MRI and re-analysis of sera for possible new markers should be informative.